Inventors and Innovators: Naval Lighterage and Anglo-American Success in the Amphibious Invasions of German-Occupied Europe - Blazich, Frank A. (The Northern Mariner / Le marin du nord, 2021)
The amphibious invasions of Sicily, Salerno, and Normandy all made ample use of US Navy landing pontoons. The simple steel box pontoons were the brainchild of civil engineer Captain John N. Laycock, who developed and perfected his inventive design on the eve of American entry into World War II. Once in the conflict, a Royal Navy reserve officer assigned to Combined Operations Headquarters, Captain Thomas A. Hussey, conceptualized innovative uses for the American pontoons for offensive amphibious operations. Working together, these men developed pontoon causeways and massive lighterage barges which ensured logistical success in the invasions of German-occupied Europe. Les invasions amphibies de la Sicile, de Salerne et de la Normandie ont toutes fait appel aux pontons de débarquement de la Marine américaine. Les simples pontons flottants en acier ont été créés par le capitaine John N. Laycock, ingénieur civil, qui a développé et perfectionné sa conception géniale à la veille de l’entrée des États-Unis dans la Seconde Guerre mondiale. Une fois le conflit déclenché, le capitaine Thomas A. Hussey, officier de réserve de la Marine royale affecté au quartier général des opérations combinées, a mis au point des utilisations novatrices des pontons américains pour les opérations amphibies offensives. La collaboration de ces deux hommes a permis de développer des chaussées de pontons et d’énormes barges de chalandage qui ont assuré le succès logistique des invasions de l’Europe occupée par les Allemands.